Development and reliability of a self-report questionnaire to examine children's perceptions of the physical activity environment at home and in the neighbourhood - Salmon Jo; Ball Kylie; Hume Clare (BMC, 2006)
Abstract Background Environmental factors are increasingly being implicated as key influences on children's physical activity. Few studies have comprehensively examined children's perceptions of their environment, and there is a paucity of literature on acceptable and reliable scales for measuring these. This study aimed to develop and test the acceptability and reliability of a scale which examined a broad range of environmental perceptions among children. Methods Based on constructs from ecological models, a survey incorporating items on children's perceptions of the physical and social environment at home and in the neighbourhood was developed. This was administered on two occasions, nine days apart, to a sample of 39 children aged 11 years (54% boys), attending a metropolitan Australian elementary school. The acceptability of the survey was determined by the proportion of missing responses to each item. The test-retest reliability of individual items, scores and scales were determined using Kappa statistics and percent agreement for categorical variables, and intraclass correlation coefficients (ICC) for continuous variables. Results There were few missing responses to each question, with only 4% of all responses missing. Although some Kappa values were low, all categorical variables showed acceptable reliability when examined for percent agreement between test and retest (range 68%-100% agreement). Continuous variables all showed moderate to good ICC values (range 0.72-0.92). Conclusion Findings suggest this questionnaire is reliable and acceptable to children for assessing environmental perceptions relevant to physical activity among 11-year-old children.